REGULASI TATA KELOLA CRYPTOCURRENCY DALAM SISTEM PEMBAYARAN DI INDONESIA - Guntoro, Guntoro; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to analyze the regulation and governance of cryptocurrency in the context of payment systems in Indonesia. The legal impact of the application of cryptocurrency, such as legal uncertainty, security risks, and potential abuse, is the focus of the research. The research method uses descriptive normative law secondary data collection techniques through literature study. Data analysis is done qualitatively. Deductive logic was used to conclude. The study's results highlighted the need for improved regulation and governance of cryptocurrency in Indonesia to create a more stable legal environment and protect the interests of all relevant parties.Keywords: Cryptocurrency, regulation, governance, payment systems, law uncertainty